2013
DOI: 10.1111/ijag.12054
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Durability of Lanthanum‐Enriched Borosilicate Glass

Abstract: The role of lanthanum in the alteration kinetics at different degrees of reaction progress was investigated at 90°C and pH 7 by complementary chemical (SIMS), morphological (SAXS), and structural (NMR, Raman, and EXAFS spectroscopy) approaches. In the first step of alteration, the forward dissolution rate diminishes with the addition of lanthanum, resembling to the behavior previously observed for zirconium. Over longer alteration time, the glasses with the highest lanthanum concentrations reach silicon satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
(131 reference statements)
4
18
0
1
Order By: Relevance
“…The initial alteration rate regime is the most likely to be directly influenced by the structural organization of a glass, in particular through polymerization of the vitreous network [56], the insertion of network formers of different natures [57], or the distribution of network modifiers [58]. These structure-reactivity correlations are however often complex to demonstrate, as numerous factors vary simultaneously when the chemical composition of the glass changes [32,59].…”
Section: Influence Of Glass Structure On the Initial Alteration Rate mentioning
confidence: 99%
“…The initial alteration rate regime is the most likely to be directly influenced by the structural organization of a glass, in particular through polymerization of the vitreous network [56], the insertion of network formers of different natures [57], or the distribution of network modifiers [58]. These structure-reactivity correlations are however often complex to demonstrate, as numerous factors vary simultaneously when the chemical composition of the glass changes [32,59].…”
Section: Influence Of Glass Structure On the Initial Alteration Rate mentioning
confidence: 99%
“…Demonstrating that upon extraction, La and Si reorganized to form Si-O-La bonds that resided in the alteration layer while the majority of other ions, B, Na and Ca leached out the glass network [26]. This ability of La to consolidate itself and other glass components of the network against 6.…”
Section: Discussionmentioning
confidence: 97%
“…Contrary to this, Angeli et al demonstrated that additions of La did not cause the formation of O 2− ions or polymerization of the network. However, La ions were confirmed by 17 O NMR and extended X-ray absorption fine structure (EXAFS) to be homogeneously dispersed within borosilicate networks and surrounded by approximately 6 NBO in mixed cation areas containing Na and Ca [25,26]. These modifying cations compensated the charge deficit surrounding La ions due the excess number of NBO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations